An Overview of Sense of Community in Dumor (Dulur Mojokerto) Art's Community - Amanda Chintya Desy; Effy Wardati Maryam (Salus Publica: Journal of Community Service, 2025)
Sense of community is very important to be applied in members in every community so that the community can survive and stand strong. This study aims to determine the description of the sense of community in the Dulur Mojokerto art community. The subjects in this study amounted to 56 people who were members of the Dulur Mojokerto art community. The method used is descriptive quantitative research, with a sense of community scale that adapts 24 sense of community Index Version Two (SCI-2) items made by Mc Milan and Cavis. Sense of community Index 2 (SCI-2) is a self-report measurement tool consisting of 24 questions, where each dimension in the sense of community is represented by 6 questions on the SCI-2, which include membership, influence, integration and fulfillment of needs, and shared emotional connection. Data analysis using descriptive analysis shows that 80% of community members have a medium sense of community, the implication of this research is to maintain the sense of community of members by doing relevant activities.